Massive Electricity Storage for a Developed Economy of Ten Billion People - William F. Pickard (IEEE Access, 2015)
Presently, America's average electrical power consumption is 1.3 kW/p; in the world as a whole, it is ~0.33 kW/p. If, for 2050, a world goal of 1 kW/p is adopted, this implies an average electric power draw of 1 GW for each population cohort of 1 000 000 residents; and the Earth will have ~10 000 such cohorts. Multi-hour outages are already common; demand peaks daily; and renewable generation is intermittent. Hence, as a hedge against rare supply failures, each cohort would profit from local backup storage of electricity/energy in the order of 1-2 GWd. For comparison, the biggest electrochemical storage scheme yet seriously proposed will contain ~240 MWh, while most of the largest pumped hydro storage reservoirs are <;50 GWh. In approximately 50 years, when fossil fuels have become scarce, we should already have constructed this bulk storage. This review argues that the principal contenders for the storage of electricity in bulk are: 1) electrochemical storage in flow batteries; 2) chemical storage in agents, such as ammonia, hydrogen, methanol, or light hydrocarbons; 3) compressed air energy storage; and 4) underground pumped hydro. Finally, it will argue that not one of these four contenders has yet been built, tested, and perfected, while virtually none of the needed storage capacity exists today.